Lithuanian polyphonic songs sutartinės: the archaic nature of their musical language in the context of global music - Velička, Eirimas (Frontiers in Psychology, 2024)
Lithuanian traditional polyphonic songs, known as sutartinės, are characterised by a distinctive musical language and have almost no analogues in world music. The aim of this article is to explore the peculiarities of their musical language and the socio-cultural context of their performance tradition in order to reveal their archaic origins. The archaic nature of sutartinės songs is shown not by individual features of their musical language, but by the totality of these features, the peculiarities of their poetics and performance traditions. An examination of the musical elements and poetry of these songs, and juxtaposition them against examples of archaic vocal polyphony from other cultures, leads to the convergence of arguments in favor of very ancient origins of these songs, possibly dating back to Old Europe (c. 3 millennium BC). A deeper insight into sutartinės songs significantly enrich our understanding of the origin and development of traditional vocal polyphony.